Curriculum Integration Model Using King’s Science and Spatial Identity to Enhance Environmental Literacy for Students in Basic Education Level - Intasingh, Somkiart; Swathanan, Sakda (Community and Social Development Journal, 2021)
Today’s environmental problems affect large number of population, which are mainly caused by human behaviors. The key mechanism for solving these problems is educational management to promote environmental literacy. This research aims to study the conditions and problems in promoting environmental literacy among students in basic education level and to design and evaluate the curriculum integration model using King’s science and spatial identity to enhance environmental literacy for the students. There are two phases of the research. Phase 1 is the study of the conditions and problems. The sample of the in-depth interview was 5 school administrators, and 5 teachers. Also, the sample for answering the questionnaire was 394 teachers. Phase 2 is the design and evaluation of curriculum integration models. The target group in the workshop were 10 teachers. Also, the population of evaluating curriculum integration model was 8 experts. Research instruments consisted of in-depth interview form, condition and problem questionnaire, workshop record form, and the model evaluation form. Data analysis was done by finding the means, standard deviations, and content analysis. The results of the research showed that 1) the condition of promoting environmental literacy in educational institutions was at a moderate level, presenting problems in enhancing environmental literacy at a high level, 2) a model of curriculum integration using King’s science and spatial identity to enhance environmental literacy has 7 components - principles of model, objectives of model, process of model, curriculum integration guidelines, measurement and evaluation, the role of the stakeholders, and success conditions, and 3) the results of the evaluation of the curriculum integration model were at a high level of propriety and feasibility.